2021
DOI: 10.1080/19942060.2020.1847199
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of a vane type pre-swirl nozzle

Abstract: Pre-swirl system is installed to minimize energy loss between the stationary and rotating parts of turbine secondary air system. Although various optimization studies were conducted to increase the pre-swirl efficiency, most of the studies were focused on a hole type pre-swirl nozzles. In this study, a vane type pre-swirl nozzle was optimized to increase mass flow rate and temperature drop for given boundary conditions. The system performance was analyzed by 3D CFD and the objective functions were used to maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Recently, the KM has extensively applied approximate complex computational models. The KM is a half parametric interpolation method, which contains the global model and local deviation [52], shown as follows:…”
Section: Kriging Modelmentioning
confidence: 99%
“…Recently, the KM has extensively applied approximate complex computational models. The KM is a half parametric interpolation method, which contains the global model and local deviation [52], shown as follows:…”
Section: Kriging Modelmentioning
confidence: 99%
“…The intersection interface transports data between the two domains. After the RMS residuals of the continuity and momentum equations are less than 10 -4 , numerical simulations are deemed to converge [26,27].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…When the local pressure drop in th nozzles is considered, the pressure drop of a TLVR will be higher than that of a rigid body [16]. Furthermore, Shen et al [17] found that the nozzles have a large number of small scale vortices and high turbulent fluctuations, which leads to high energy dissipation Thus, Lee et al [18] and Liu et al [19] proposed vane-shaped nozzles to reduce the loca pressure drop. It is worth noting that the collaborative optimization of multiple geomet rical parameters of nozzles is a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the collaborative optimization of multiple geomet rical parameters of nozzles is a challenge. In recent years, using high-dimensional surro gate models for predicting the effects of multiple geometrical parameters has become an acceptable approach [18,20,21].…”
Section: Introductionmentioning
confidence: 99%